Aspectos políticos na obra cinematográfica de Kleber Mendonça Filho - Santos, Geovanna Pirillo Carnevalle dos (2023)
Kleber Mendonça Filho's film productions, as he himself states, have a chronic character in reporting vital aspects of Brazilian society. Based on this principle, our goal is to delve into these films as a field, conducting an ethnocartographic observation of this territory, scrutinizing aspects of necropolitics present therein. Observing them in these films is akin to observing them in the social, economic, cultural, and subjective structure of our country. Necropolitics involves assuming the permanence of a state of exception for a specific population. It relies on scientific and racial fallacies to perpetuate a regime of death, inciting fear and violence in the name of sustaining an economic and geopolitical system that consumes lives with a sense of disposability. To provide such an observation of how this concept is disseminated, we will draw from various authors, especially Achille Mbembe, Michel Foucault, Marilena Chaui, and Jessé Souza. The films "Neighboring Sounds" (2012), "Aquarius" (2016), and "Bacurau" (2019) are the primary subjects of study for the mentioned issues, which have framed vital provocations on the screens of Brazil and the world, contributing to our resistance against cyclical and active violence.